PAK Dalam Pembentukan Identitas Remaja di Jemaat KGMPI Elohim Melonguane Kabupaten Kepulauan Talaud - Kezia Mambu (MAGENANG : Jurnal Teologi dan Pendidikan Kristen, 2024)
Abstract: The purpose of this study is to determine the formation of Christian teenagers' identity through church and family Christian Religious Education. The research was conducted using a qualitative descriptive approach. Data were collected through observations and interviews with adolescents, parents, special ministers, and congregational pastors. The results of data analysis and interpretation indicate that: (1) Christian youth identity formation through PAK has been carried out by the church and family, but still requires more cooperation, both in active programs and enthusiasm of adolescents to worship, (2) The inhibiting factors in the formation of adolescent identity are adolescents themselves, parents, and peers. Based on these findings, it is suggested that the special service commission should be able to embrace adolescents who are not yet active from worship fellowship and church activities through more active programs and establish cooperation with parents. Parents still provide motivation and examples so that adolescents grow in the knowledge of God's love so that it radiates from thoughts, words and behavior. Thus, the formation of Christian adolescent identity is very important for adolescents so that they know themselves as a whole and believe in the Lord Jesus Christ as their personal Lord and Savior.